Epidemiology and Burden of Cholera in Nigeria (African Journal of Biomedical Research, 2024)
Cholera is an acute diarrhoeal infection caused by ingestion of food or water contaminated with bacterium Vibrio cholera. It is a significant public health concern globally, particularly in low income countries like Nigeria and resulting in mobility and mortality every year. Several factors including socioeconomic and environmental among other factors drive this trend. Some regions in the country have been identified as hot spots most especially the north where insurgency has worsened outbreaks and management/control difficult. This review examines the occurrence, geographical distribution, seasonal patterns, risk factors and associated mortality rates with cholera outbreaks highlighting the key findings and trends observed in the epidemiology of cholera and the challenges faced in the prevention and control of cholera in the country such as; inadequate sanitation and water supply, limited healthcare resources and low community awareness. Furthermore, It highlight the need for improved surveillance systems, access to clean water and sanitation facilities, improved education on the importance of handwashing and good hygiene practices with effective public health intervention to mitigate the burden of cholera especially in the northern part of Nigeria where the outbreaks are more frequent. It contributes to the existing literature on cholera epidemiology in Nigeria and provides valuable insights for future research and intervention strategies